Preparation method and application of MOFs material for removing microplastics in water body
Patent Information
- Application Number
- CN202410594840.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-14
AI Technical Summary
[0009]另外,尽管MOFs材料以其独特的结构和性能特点广受研究者的青睐,然而在实际应用中,由于MOFs材料表面能较高,容易在使用中发生团聚,降低其反应活性
[0028]1、氧化锆与氧化铈配合使用形成ZrO2/CeO2共聚晶体纳米纤维,所包含的Zr和Ce作为惰性金属具有良好的耐腐蚀性,使得复合材料在pH 8-10.4范围具有良好稳定性。尤其六水合硝酸铈添加量4.11wt%、八水合氯氧化锆添加量54.06wt%、氯化钾添加量15.11wt%、谷氨酰胺添加量26.72wt%以及pH值为10.1时吸光度值仅为0.15,稳定性最好,提高了MOFs材料在中碱性水体中吸附去除微塑料的稳定性。
Smart Images

Figure CN118384869B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of polymer material preparation, specifically to a method for preparing MOFs materials for removing microplastics from water and their application. Background Technology
[0002] Microplastics are defined as small plastic pollutants with a diameter of less than 5 mm. Plastic products are widely used in cosmetics, textiles, packaging materials, agriculture, and building materials due to their lightweight and durable properties. A large portion of used waste plastics is discharged into the aquatic environment during human production and daily life. These plastics gradually break down into small plastic particles, or microplastics, at the millimeter, micrometer, or even nanometer scale, through physical, chemical, and biological degradation processes. Common types of microplastics include polyethylene (PE), polypropylene (PP), and polystyrene (PS).
[0003] The small size of microplastics makes them easier for aquatic organisms to ingest and accumulate. When low-trophic-level aquatic organisms ingest microplastics, the lack of substances in their bodies to break them down allows the microplastics to be passed through the food chain, eventually reaching the highest trophic level – the human body. It has been proven that the accumulation of microplastics in objects has varying degrees of impact on the survival rate, growth rate, age at first reproduction, reproductive time, and total number of offspring in aquatic organisms. In addition to their own toxic effects, microplastics readily combine with pollutants in water bodies, such as heavy metals and persistent organic pollutants, to form complex toxic substances.
[0004] Microplastic removal technologies include filtration, adsorption, coagulation, photocatalysis, biodegradation, membrane bioreactors, and magnetic separation. Various functional materials have emerged for removing microplastics from water through adsorption, coagulation, flocculation, flotation, and magnetic separation. These functional materials include Fe3O4 nanoparticles, amine-modified silica aerogels, chitin, and graphene oxide sponges. MOFs (Metal-Oxide-Factory Materials) stand out among these materials due to their significant potential for adsorbing and removing microplastics from aquatic environments. They exhibit superior adsorption performance, and using functionalized MOFs with specific groups or elemental combinations can increase their affinity for plastic particles.
[0005] MOFs, also known as coordination polymers, are a class of highly ordered porous crystalline hybrid materials composed of metal clusters and multifunctional organic linkers. They can form one-dimensional, two-dimensional, or three-dimensional crystal structures through coordination between metal ions or clusters and organic ligands. These MOFs possess properties including good crystallinity, tunable ultra-high porosity, variable structure, large surface area and uniform pore volume, specific interaction sites for selected adsorbates, excellent photoelectric properties, and high thermal and mechanical stability. Furthermore, MOFs are more efficient and advanced than traditional adsorbents, exhibiting superior adsorption capacity and excellent physicochemical properties. In recent years, MOFs have begun to be applied to the removal of microplastics from water and wastewater.
[0006] Chinese Patent 202011633050.5 discloses a method for "the application of MOFs fiber membranes in the adsorption and retention of micro- and nano-plastics in water". The method involves swelling a modified fiber fabric in a mixed solution of long-chain carboxyl organic ligands and protein to simulate the biomimetic mineralization of proteins, and then assembling it in situ with zinc ions to obtain a MOFs fiber membrane. This invention utilizes the distribution of nano-MOF crystalline particles within the swollen pores of cellulose fibers to prepare a composite membrane material with a large specific surface area, enabling efficient adsorption and retention of micro- and nano-plastics in water. However, prolonged use leads to membrane clogging, and the invention does not further explain how to remove the adsorbed and retained micro-plastics, nor does it address the poor recyclability of the MOFs fiber membrane.
[0007] Another issue to note is that, on the one hand, the stability of MOF materials in water is crucial for achieving their adsorption function. To address the poor stability of MOF materials in water, Chinese Patent 202210263346.5 discloses "Preparation and Application of an Aqueous Stable MOFs / Graphite Phase Carbon Nitride Composite Material". This invention discloses a method for preparing the MOFs / wt%-C3N4 composite material, which involves mixing and grinding MOFs and wt%-C3N4 materials, calcining to remove excess substances, and then vacuum drying to obtain the MOFs / wt%-C3N4 composite material. The main mechanism by which this material maintains its stability in water is that, during thermal exfoliation, the graphite phase carbon nitride material gradually coats the surface of the MOFs material through electrostatic interactions. The resulting film effectively blocks water molecules from further approaching the metal ion centers, thus providing an activation energy barrier that needs to be overcome and effectively improving the hydrophobicity of the MOFs material.
[0008] On the other hand, some water-stable MOFs, such as MIL-53, MIL-100, MIL-101, MIL-125, and Uio-66, cannot achieve specific adsorption of microplastics of a certain size. The pore size and shape need to be adjusted to correspond to the size of the microplastics to enhance the possibility of adsorption, capture, and retention. In addition, Wan et al. studied the adsorption and removal of PS microplastics by ZIF-67 (H.Wan, J.Wanwt%, X.Shenwt%, et al. Removal of polystyrene microplastics from aqueous solution usinwt% the metal-orwt% anic framework material of ZIF-67, Toxics 10(2022)70). The literature shows that the material maintained a stable adsorption rate of approximately 88.3% in the pH range of 3–10, but under strongly alkaline conditions (pH 11–12), the adsorption efficiency dropped to 64.4%. The obtained MOF materials have poor resistance to alkaline environmental conditions.
[0009] Furthermore, although MOF materials are widely favored by researchers due to their unique structure and performance characteristics, in practical applications, their high surface energy makes them prone to aggregation during use, reducing their reactivity. As nano-copolymeric crystal materials, improper separation during use also poses a risk of secondary pollution.
[0010] Therefore, a method for preparing MOFs materials for removing microplastics from water and their application are proposed. Summary of the Invention
[0011] The purpose of this invention is to provide a method for preparing MOFs materials for removing microplastics from water and their application. By preparing ZrO2 / CeO2 flexible nanofibers ZCNM, further reacting to obtain ZCNM-UiO-66-NH2 composite material, and then washing and desorbing with sodium hydroxide solution to obtain recyclable material, the invention achieves good alkali resistance, dispersibility, adsorption and removal of microplastics, hydrophobicity, and recyclability of MOFs materials.
[0012] To achieve the above objectives, the present invention provides the following technical solution:
[0013] A method for preparing MOFs materials for removing microplastics from water, characterized by comprising the following steps:
[0014] Preparation of S1 ZrO2 / CeO2 flexible nanofibers: A mixed solution was obtained by dissolving 0wt%-5.36wt% cerium nitrate hexahydrate and 31.35-60.74wt% zirconium oxychloride octahydrate. A soluble salt and a carbonyl compound were added to the mixed solution, and the solution was heated to dissolve and concentrate to a viscous state. The solution was then combusted in a furnace and filtered and washed to obtain zirconium oxide / cerium oxide nanopolymer crystals. The nanopolymer crystals were dissolved in a mixed solution of DMF and THF, and polyacrylonitrile was added. The solution was stirred until completely dissolved and then allowed to stand to obtain a precursor spinning sol. The precursor spinning sol was electrospun to obtain ZrO2 / CeO2 precursor fibers. The precursor fibers were collected in a drum and then heated to 600℃ in a muffle furnace to obtain flexible ZrO2 / CeO2 nanofibers ZCNM.
[0015] Preparation of S2 ZCNM-UiO-66-NH2 composite material: 10-35 wt% of ZCNM was dissolved in 10 mL of a mixed solution of DMF and THF to obtain a ZCNM solution with a volume ratio of 55-100:0-45; ZrCl4 and 2-aminoterephthalic acid in a molar ratio of 1:1 were dissolved in 70 mL of the mixed solution, and hydrofluoric acid with a molar amount of 1.1-3.2 times that of ZrCl4 was added. The mixture was stirred at room temperature to obtain a homogeneous liquid; 10-65 wt% of the homogeneous liquid was added to the ZCNM solution, and the mixture was sonicated for 15 min. The mixture was then poured into a stainless steel autoclave. The solid obtained after the reaction was washed and dried to obtain the ZCNM-UiO-66-NH2 composite material.
[0016] Preparation of S3 ZCNM-UiO-66-NH2-PTEF composite material: 0-70wt% polytetrafluoroethylene emulsion was dropped into the ZCNM-UiO-66-NH2 material suspension under ultrasonic conditions, and the mixture was continuously sonicated. The mixture was then placed in liquid nitrogen for freezing, thawed, and dried to remove moisture, thus obtaining the ZCNM-UiO-66-NH2-PTEF composite material.
[0017] S4 Recyclable Material Preparation: MOFs material with adsorbed microplastics; sodium hydroxide solution is added to the MOFs material to wash and desorb the microplastics, and the cycle is repeated 1-5 times.
[0018] Preferably, the amount of cerium nitrate hexahydrate added in S1 is 2.17-5.36 wt%.
[0019] Preferably, the soluble salt in S1 is either potassium chloride (KCl) or cesium chloride (CsCl); and the carbonyl compound is either glutamine or malonic anhydride.
[0020] Preferably, the amount of KCl added is 14.23-31.34 wt%; the amount of CsCl added is 25.17-50.78 wt%; the amount of glutamine added is 15.49-36.59 wt%; and the amount of malonic anhydride added is 14.56-31.00 wt%.
[0021] Preferably, the amount of ZCNM added in S2 is one of 10, 20, 30, or 35 wt%; the volume ratio of the DMF and THF mixed solution is one of 55:45, 100:0, 60:40, 70:30, or 80:20; and the amount of the homogeneous liquid added is one of 10, 20, 30, 35, 40, or 65 wt%.
[0022] Preferably, the amount of hydrofluoric acid added in S2 is 3.2 times the molar amount of ZrCl4.
[0023] Preferably, the amount of polytetrafluoroethylene added in S3 is one of 0, 35, 40, 55, 60, or 70 wt%.
[0024] Preferably, the pH value of the sodium hydroxide solution in step S4 is 10; and the washing time is 10 min.
[0025] Preferably, the number of cycles in S4 is one of 1, 2, 3, 4, or 5.
[0026] An application of a MOFs material for removing microplastics from water is characterized by: the MOFs material for removing microplastics from water; the MOFs material for removing microplastics from water is obtained by further electrospinning of synthesized zirconium oxide / cerium oxide nanopolymer crystals to obtain flexible nanofibers ZCNM, which are then subjected to a solvothermal synthesis reaction with ZrCl4 and 2-aminoterephthalic acid to obtain a ZCNM-UiO-66-NH2 composite material, and finally encapsulated with polytetrafluoroethylene; it is applied to the removal of microplastics from water; the pH of the water is 8-10.4, the type of microplastic is PS, and the diameter of the microplastic is 90nm-15μm; the zirconium oxide and cerium oxide are used in combination, so that the composite material is suitable for the removal of microplastics from water at pH 8-10.4. The MOFs exhibit good stability within the 8-10.4 range. The addition of ZCNM, DMF, THF, and the homogeneous liquid in a fixed ratio improves the dispersibility of the MOFs material, achieving a fiber diameter of 4.32 μm. The hydrofluoric acid adjusts the pore size, providing good adsorption capacity for PS microplastics in the 90 nm-15 μm range. The ZCNM-UiO-66-NH2-PTEF material prepared from polytetrafluoroethylene has a contact angle of 158° and good hydrophobicity. By controlling the pH of the sodium hydroxide solution to remove the MOFs material that has adsorbed microplastics, the adsorption efficiency of the MOFs material can still reach over 80% after 5 cycles, demonstrating good recyclability.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] 1. Zirconia and cerium oxide are used in combination to form ZrO2 / CeO2 copolymer nanofibers. The Zr and Ce contained within, as inert metals, exhibit good corrosion resistance, resulting in good stability of the composite material within a pH range of 8-10.4. In particular, the best stability is achieved with the addition of 4.11 wt% cerium nitrate hexahydrate, 54.06 wt% zirconium oxychloride octahydrate, 15.11 wt% potassium chloride, and 26.72 wt% glutamine, and an absorbance value of only 0.15 at a pH of 10.1. This improves the stability of MOF materials in adsorbing and removing microplastics in moderately alkaline water.
[0029] 2. The addition of flexible nanofibers ZCNM, DMF, and THF to a homogeneous liquid in a fixed ratio improved the dispersibility of the ZCNM-UiO-66-NH2 composite material. When the ZCNM addition amount was 20wt%, the volume ratio of the DMF and THF mixed solution was 55:45, and the homogeneous liquid addition amount was 40wt%, the fiber diameter of the material could reach 4.32μm. The large loading of flexible nanofibers increased the specific surface area of the final composite material, and the resulting composite material was not prone to agglomeration and had good dispersibility.
[0030] 3. Adding hydrogen fluoride to adjust the pore size of MOF materials. The binding of fluoride ions to zirconium not only compensates for the framework charge imbalance caused by the missing linkers, but also competes with the linkers for coordination with zirconium metal centers, controlling the nucleation and growth process of UiO-66 crystals, thereby controlling the pore size of MOF materials and achieving the goal of removing 20nm-60μm microplastics. In particular, the adsorption effect is best when the addition amount of ZrCl4 and 2-aminoterephthalic acid is 18.5mmol and the addition amount of hydrofluoric acid is 59.20mmol (the molar amount of hydrofluoric acid is 3.2 times that of ZrCl4 / 2-aminoterephthalic acid), and the adsorption efficiency for 800nm PS microplastics can reach 94.1%.
[0031] 4. The ZCNM-UiO-66-NH2-PTEF material prepared from polytetrafluoroethylene exhibits good hydrophobicity. The ZCNM-UiO-66-NH2-PTEF composite material prepared with 40wt% polytetrafluoroethylene can achieve a superhydrophobic effect, improving the stability of MOF materials in adsorbing and removing microplastics in water.
[0032] 5. The MOFs material that has adsorbed microplastics was cleaned and desorbed using sodium hydroxide solution, and then reused for adsorbing microplastics. After 5 cycles, the adsorption efficiency of the MOFs material can still reach more than 80%, demonstrating good recyclability. This improves the recyclability of the composite material. Attached Figure Description
[0033] Figure 1 This is a graph showing the acid and alkali resistance of the MOFs material prepared in Example 21 of this invention.
[0034] Figure 2 The image shows the adsorption effect of MOFs material with different particle sizes on PS microplastics prepared in Example 49 of this invention.
[0035] Figure 3 This is a diagram showing the effect of MOFs material prepared in Example 56 of the present invention on the adsorption of microplastics during recycling. Detailed Implementation
[0036] The purpose of this invention is to provide a MOF material for removing microplastics from water and its preparation method. By using polyoxyethylene octylphenol ether-10 as an emulsifier and ammonium persulfate as an initiator for waterborne acrylate emulsion polymerization, and then functionalizing the surface of the emulsion with chitosan after emulsion polymerization, a waterborne high-temperature and acid-resistant coating with non-settling properties, high yield, and strong water resistance is prepared.
[0037] To achieve the above objectives, the present invention provides the following technical solution:
[0038] A MOFs material for removing microplastics from water and its preparation method, characterized by comprising the following steps:
[0039] Example 1
[0040] Preparation of S1 ZrO2 / CeO2 flexible nanofibers: 4.11 wt% cerium nitrate hexahydrate and 54.06 wt% zirconium oxychloride octahydrate were dissolved in a mixed solution of 15 g methanol and 2 g deionized water. 15.11 wt% potassium chloride and 26.72 wt% glutamine were added to the mixed solution. After heating to dissolve, the solution was concentrated to a viscous state and then burned in a furnace at 500℃. After combustion, the product was filtered and washed with deionized water until the conductivity of the washing solution was below 10 μS / cm. 2Zirconia / cerium oxide nanopolymer crystals were obtained; the nanopolymer crystals were dissolved in a mixed solution of 20 mL dimethylformamide (DMF) and tetrahydrofuran (THF), and then 0.101 wt% polyacrylonitrile was added. After stirring until completely dissolved, the solution was left to stand overnight to form a precursor spinning sol. The precursor spinning sol was added to a syringe, and electrospinning was performed using a stainless steel needle at a feed rate of 0.84 mL / h, an applied spinning voltage of 12 kV, a spinning temperature of 25 °C, a spinning degree of 35%, and a receiving distance of 20 cm. ZrO2 / CeO2 precursor fibers were collected using a roller with a diameter of 50 mm, a translational speed of 10 mm / s, and a rotational speed of 600 r / min. The ZrO2 / CeO2 precursor fibers were gradually heated to 600℃ in a muffle furnace and held at that temperature for 2 hours to remove organic matter from the ZrO2 / CeO2 precursor fibers. The fibers were then allowed to cool naturally to obtain flexible ZrO2 / CeO2 nanofibers (ZCNM).
[0041] Preparation of S2 ZCNM-UiO-66-NH2 composite material: Based on the mass of ZCNM-UiO-66-NH2-PTEF composite material, 20 wt% of ZCNM was added and dissolved in 10 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF); 18.5 mmol of ZrCl4 and 18.5 mmol of 2-aminoterephthalic acid were dissolved in 70 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF) (V:V = 50:50), and 59.2 mmol of hydrofluoric acid was added (the amount of hydrofluoric acid added was 3.2 times the molar amount of ZrCl4). A homogeneous solution was obtained by stirring at room temperature. 40 wt% of the homogeneous solution was added to the ZCNM solution. After ultrasonic treatment for 15 min, the obtained mixture was poured into a sealed 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and then placed in a vacuum drying oven at 120 °C for 50 h. The solid obtained after the reaction was washed three times with DMF and then three times with methanol. It was then dried in a vacuum drying oven at 80°C for 12 hours to obtain the ZCNM-UiO-66-NH2 composite material.
[0042] Preparation of S3 ZCNM-UiO-66-NH2-PTEF composite material: The composite material is composed of ZCNM-UiO-66-NH2 material encapsulated by polytetrafluoroethylene (PTFE). A 40 wt% PTFE emulsion was added dropwise to a ZCNM-UiO-66-NH2 material suspension under ultrasonic conditions. The mixture was continuously sonicated, then frozen in liquid nitrogen. After thawing, the moisture was removed, and the mixture was dried to obtain the ZCNM-UiO-66-NH2-PTEF composite material based on PTFE-encapsulated MOFs.
[0043] Example 2-20
[0044] Unlike Example 1, the amounts of substances added in Examples 2-20 changed, as shown in Table 1. Additionally, cerium nitrate hexahydrate and zirconium oxychloride octahydrate were not added in Example 10.
[0045] Table 1. Changes in the amount of cerium nitrate hexahydrate, zirconium oxychloride octahydrate, KCl, CsCl, glutamine, and malonic anhydride added.
[0046]
[0047] Example 21
[0048] The MOFs materials obtained in Examples 1-20 were subjected to pH stability testing. First, sodium hydroxide particles were completely dissolved in distilled water to achieve a hydroxide ion concentration of 0.0015 mol / L. The pH value of the sodium hydroxide solution was adjusted using hydrochloric acid solution and measured with a pH meter, resulting in solutions with pH values of 6, 7, 8, 8.3, 9, 9.6, 10.1, 10.4, and 11. 60 mwt% of each of the MOFs materials obtained in Examples 1-20 were accurately weighed and placed in 60 mL of each of the nine pH solutions. The solutions were then sonicated for 20 min (4000 W). The resulting liquids were rapidly diluted 50-fold, and 100 μL of each solution was placed in a 96-well plate. The absorbance of the liquids was measured at OD540 nm. Each sample was tested in parallel six times, and the average value was taken. Representative results were recorded. The test results are shown below. Figure 1 As shown.
[0049] A higher absorbance value indicates a less stable material, making it unable to maintain the structure and morphology of the prepared MOFs. The results show that the materials obtained in all examples exhibit significantly higher stability in the pH range of 8-10.4 compared to other pH environments. This is because the ZCNM-UiO-66-NH2-PTEF composite material contains basic amino groups, making it suitable for stable existence in alkaline environments. Compared to Examples 1-9, the material obtained in Example 10 without the addition of cerium nitrate hexahydrate showed the worst stability in the pH range of 6-11. This is because the cerium nitrate hexahydrate added in Examples 1-9 formed a tetragonal crystal structure with zirconium oxychloride octahydrate during the entire reaction process and stably assembled with UiO-66-NH2, improving the material's stability. Furthermore, Zr and Ce in ZrO2 and CeO2 are inert metals, further enhancing the stability of the ZCNM-UiO-66-NH2-PTEF composite material in the pH range of 8-10.4. The MOFs material exhibited the best stability when the addition amounts of cerium nitrate hexahydrate (0.2683 wt%), zirconium oxychloride octahydrate (3.5315 wt%), potassium chloride (15.11 wt%), glutamine (1.7454 wt%), and pH value (10.1) were particularly high.
[0050] Example 22
[0051] Preparation of S1 ZrO2 / CeO2 flexible nanofibers: 0.2683 wt% cerium nitrate hexahydrate and 3.5315 wt% zirconium oxychloride octahydrate were dissolved in a mixed solution of 15 wt% methanol and 2 wt% deionized water. 15.11 wt% potassium chloride and 1.7454 wt% glutamine were added to the mixed solution. After heating to dissolve, the solution was concentrated to a viscous state and then burned in a furnace at 500℃. After combustion, the product was filtered and washed with deionized water until the conductivity of the washing solution was below 10 μS / cm. 2 Zirconia / cerium oxide nanopolymer crystals were obtained; the nanopolymer crystals were dissolved in a mixed solution of 20 mL dimethylformamide (DMF) and tetrahydrofuran (THF), and then 0.101 wt% polyacrylonitrile was added. After stirring until completely dissolved, the solution was left to stand overnight to form a precursor spinning sol. The precursor spinning sol was added to a syringe, and electrospinning was performed using a stainless steel needle at a feed rate of 0.84 mL / h, an applied spinning voltage of 12 kV, a spinning temperature of 25 °C, a spinning degree of 35%, and a receiving distance of 20 cm. ZrO2 / CeO2 precursor fibers were collected using a roller with a diameter of 50 mm, a translational speed of 10 mm / s, and a rotational speed of 600 r / min. The ZrO2 / CeO2 precursor fibers were gradually heated to 600℃ in a muffle furnace and held at that temperature for 2 hours to remove organic matter from the ZrO2 / CeO2 precursor fibers. The fibers were then allowed to cool naturally to obtain flexible ZrO2 / CeO2 nanofibers (ZCNM).
[0052] Preparation of S2 ZCNM-UiO-66-NH2 composite material: Based on the mass of ZCNM-UiO-66-NH2-PTEF composite material, 10 wt% of ZCNM was added and dissolved in 10 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF); 18.5 mmol of ZrCl4 and 18.5 mmol of 2-aminoterephthalic acid were dissolved in 70 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF) (V:V = 100:0), and 59.2 mmol of hydrofluoric acid was added (the amount of hydrofluoric acid added was 3.2 times the molar amount of ZrCl4). A homogeneous solution was obtained by stirring at room temperature. 40 wt% of the homogeneous solution was added to the ZCNM solution. After ultrasonic treatment for 15 min, the obtained mixture was poured into a sealed 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and then placed in a vacuum drying oven at 120 °C for 50 h. The solid obtained after the reaction was washed three times with DMF and then three times with methanol. It was then dried in a vacuum drying oven at 80°C for 12 hours to obtain the ZCNM-UiO-66-NH2 composite material.
[0053] Preparation of S3 ZCNM-UiO-66-NH2-PTEF composite material: The composite material is composed of ZCNM-UiO-66-NH2 material encapsulated by polytetrafluoroethylene (PTFE). A 40 wt% PTFE emulsion was added dropwise to a ZCNM-UiO-66-NH2 material suspension under ultrasonic conditions. The mixture was continuously sonicated, then frozen in liquid nitrogen. After thawing, the moisture was removed, and the mixture was dried to obtain the ZCNM-UiO-66-NH2-PTEF composite material based on PTFE-encapsulated MOFs.
[0054] Examples 23-38
[0055] Unlike Example 22, the material composition ratios in Examples 23-38 have been changed, as shown in Table 2.
[0056] Table 2 Material Composition and Proportioning
[0057] Example 23 10 55:45 20 Example 24 10 100:0 40 Example 25 10 55:45 40 Example 26 20 100:0 20 Example 27 20 55:45 20 Example 28 20 100:0 40 Example 29 20 55:45 40 Example 30 10 100:0 30 Example 31 10 55:45 30 Example 32 20 100:0 30 Example 33 20 55:45 30 Example 34 20 60:40 40 Example 35 20 70:30 40 Example 36 20 80:20 40 Example 37 15 100:0 40 Example 38 15 55:45 40
[0058] Example 39
[0059] The composite materials prepared in Examples 22-38 were analyzed by scanning electron microscopy. Scanning electron microscopy (SEM) images were obtained using a Phenom wt%SR benchtop electron microscope. Typical instrument settings used an accelerating voltage of 5 kV and a nominal working distance of 10 mm. Fiber diameters were automatically analyzed using the Phenom Fibermetric software package. Fiber diameters in the composite materials are shown in Table 3.
[0060] Table 3 Fiber diameter of ZCNM-UiO-66-NH2 material
[0061]
[0062]
[0063] When the ZCNM addition amount was 10 wt%, the fiber diameter did not increase with the change in the DMF:THF volume ratio or the increase in the UiO-66-NH2 polymer addition. However, with 20 wt% ZCNM and a DMF:THF ratio of 55:45, the fiber diameter increased with the increase in polymer percentage, indicating that the fiber loading increased with the increase in polymer content. Compared with pure DMF solvent, the ZCNM-UiO-66-NH2 composite material obtained from DMF / THF exhibited multiple protofibrils aggregated into larger fiber bundles. This is because UiO-66-NH2 selectively deposits within and on the surface of the fibers in the mixed solvent system, resulting in better dispersibility and a larger fiber loading capacity.
[0064] Example 40
[0065] Preparation of S1 ZrO2 / CeO2 flexible nanofibers: 4.11 wt% cerium nitrate hexahydrate and 54.06 wt% zirconium oxychloride octahydrate were dissolved in a mixed solution of 15 g methanol and 2 g deionized water. 15.11 wt% potassium chloride and 26.72 wt% glutamine were added to the mixed solution. After heating to dissolve, the solution was concentrated to a viscous state and then burned in a furnace at 500℃. After combustion, the product was filtered and washed with deionized water until the conductivity of the washing solution was below 10 μS / cm. 2 Zirconia / cerium oxide nanopolymer crystals were obtained; the nanopolymer crystals were dissolved in a mixed solution of 20 mL dimethylformamide (DMF) and tetrahydrofuran (THF), and then 0.101 wt% polyacrylonitrile was added. After stirring until completely dissolved, the solution was left to stand overnight to form a precursor spinning sol. The precursor spinning sol was added to a syringe, and electrospinning was performed using a stainless steel needle at a feed rate of 0.84 mL / h, an applied spinning voltage of 12 kV, a spinning temperature of 25 °C, a spinning degree of 35%, and a receiving distance of 20 cm. ZrO2 / CeO2 precursor fibers were collected using a roller with a diameter of 50 mm, a translational speed of 10 mm / s, and a rotational speed of 600 r / min. The ZrO2 / CeO2 precursor fibers were gradually heated to 600℃ in a muffle furnace and held at that temperature for 2 hours to remove organic matter from the ZrO2 / CeO2 precursor fibers. The fibers were then allowed to cool naturally to obtain flexible ZrO2 / CeO2 nanofibers (ZCNM).
[0066] Preparation of S2 ZCNM-UiO-66-NH2 composite material: Based on the mass of ZCNM-UiO-66-NH2-PTEF composite material, 10 wt% of ZCNM was added and dissolved in 10 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF); 18.5 mmol of ZrCl4 and 18.5 mmol of 2-aminoterephthalic acid were dissolved in 70 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF) (V:V = 100:0), and 18.5 mmol of hydrofluoric acid was added (the amount of hydrofluoric acid added was 1.1 times the molar amount of ZrCl4). A homogeneous solution was obtained by stirring at room temperature. 40 wt% of the homogeneous solution was added to the ZCNM solution. After ultrasonic treatment for 15 min, the obtained mixture was poured into a sealed 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and then placed in a vacuum drying oven at 120 °C for 50 h. The solid obtained after the reaction was washed three times with DMF and then three times with methanol. It was then dried in a vacuum drying oven at 80°C for 12 hours to obtain the ZCNM-UiO-66-NH2 composite material.
[0067] Preparation of S3 ZCNM-UiO-66-NH2-PTEF composite material: The composite material is composed of ZCNM-UiO-66-NH2 material encapsulated by polytetrafluoroethylene (PTFE). A 45 wt% PTFE emulsion was added dropwise to a ZCNM-UiO-66-NH2 material suspension under ultrasonic conditions. The mixture was continuously sonicated, then frozen in liquid nitrogen. After thawing, the moisture was removed, and the mixture was dried to obtain the ZCNM-UiO-66-NH2-PTEF composite material based on PTFE-encapsulated MOFs.
[0068] Examples 41-48
[0069] Unlike Example 40, the amounts of ZrCl4, 2-aminoterephthalic acid, and hydrofluoric acid added in Examples 41-48 were changed, as shown in Table 4.
[0070] Table 4. Addition amounts of ZrCl4, 2-aminoterephthalic acid, and hydrofluoric acid
[0071]
[0072] Example 49
[0073] The adsorption performance of MOF composite materials prepared in Examples 40-48 on microplastics of different sizes was determined. 650 mg of monodisperse PS (XFJ100, Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.) with different particle sizes (20 nm, 90 nm, 200 nm, 800 nm, 1 μm, 15 μm, and 60 μm) were dispersed in water. 650 mg of ZCNM-UiO-66-NH2-PTEF composite material was added, and the adsorption efficiency of the MOF composite material after 60 min of adsorption of microplastics was investigated in an aqueous environment at 25 °C and pH 10.1.
[0074] The amount of hydrofluoric acid added varied with the reactant concentration. The addition of hydrofluoric acid promoted the growth of micron-sized UiO-66-NH2 crystals. This crystal growth trend is consistent with a coordination modulation mechanism, meaning that the hydrofluoric acid modulator influences the growth of UiO-66-NH2 through coordination with secondary building units during framework formation. The adsorption effect was optimal, reaching an adsorption efficiency of 94.1%, when the amounts of ZrCl4 and 2-aminoterephthalic acid were 18.5 mmol and the amount of hydrofluoric acid was 59.20 mmol. (Specific details are omitted as they are not provided in the original text.) Figure 2As shown, fluoride ions, due to their high electronegativity, directly bind to Zr in the secondary building blocks of the MOF framework. This binding of fluoride ions to Zr not only compensates for the framework charge imbalance caused by missing linkers but also competes with linkers for coordination with Zr metal centers, thereby controlling the nucleation and growth process of UiO-66 crystals. The introduction of fluoride enables pore size tuning of UiO-66-NH2, allowing it to exhibit good adsorption performance for microplastics in the 90nm-15μm range.
[0075] Example 50
[0076] Preparation of S1 ZrO2 / CeO2 flexible nanofibers: 4.11 wt% cerium nitrate hexahydrate and 54.06 wt% zirconium oxychloride octahydrate were dissolved in a mixed solution of 15 g methanol and 2 g deionized water. 15.11 wt% potassium chloride and 26.72 wt% glutamine were added to the mixed solution. After heating to dissolve, the solution was concentrated to a viscous state and then burned in a furnace at 500℃. After combustion, the product was filtered and washed with deionized water until the conductivity of the washing solution was below 10 μS / cm. 2 Zirconia / cerium oxide nanopolymer crystals were obtained; the nanopolymer crystals were dissolved in a mixed solution of 20 mL dimethylformamide (DMF) and tetrahydrofuran (THF), and then 0.101 wt% polyacrylonitrile was added. After stirring until completely dissolved, the solution was left to stand overnight to form a precursor spinning sol. The precursor spinning sol was added to a syringe, and electrospinning was performed using a stainless steel needle at a feed rate of 0.84 mL / h, an applied spinning voltage of 12 kV, a spinning temperature of 25 °C, a spinning degree of 35%, and a receiving distance of 20 cm. ZrO2 / CeO2 precursor fibers were collected using a roller with a diameter of 50 mm, a translational speed of 10 mm / s, and a rotational speed of 600 r / min. The ZrO2 / CeO2 precursor fibers were gradually heated to 600℃ in a muffle furnace and held at that temperature for 2 hours to remove organic matter from the ZrO2 / CeO2 precursor fibers. The fibers were then allowed to cool naturally to obtain flexible ZrO2 / CeO2 nanofibers (ZCNM).
[0077] Preparation of S2 ZCNM-UiO-66-NH2 composite material: Based on the mass of ZCNM-UiO-66-NH2-PTEF composite material, 20 wt% of ZCNM was added and dissolved in 10 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF); 18.5 mmol of ZrCl4 and 18.5 mmol of 2-aminoterephthalic acid were dissolved in 70 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF) (V:V = 50:50), and 59.2 mmol of hydrofluoric acid was added (the amount of hydrofluoric acid added was 3.2 times the molar amount of ZrCl4). A homogeneous solution was obtained by stirring at room temperature. 40 wt% of the homogeneous solution was added to the ZCNM solution. After ultrasonic treatment for 15 min, the obtained mixture was poured into a sealed 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and then placed in a vacuum drying oven at 120 °C for 50 h. The solid obtained after the reaction was washed three times with DMF and then three times with methanol. It was then dried in a vacuum drying oven at 80°C for 12 hours to obtain the ZCNM-UiO-66-NH2 composite material.
[0078] Preparation of S3 ZCNM-UiO-66-NH2-PTEF composite material: The composite material is made by encapsulating ZCNM-UiO-66-NH2 material with polytetrafluoroethylene (PTFE). 18.36 wt% PTFE and 9.18 wt% Tween 80 were mixed with water to obtain a PTFE emulsion. 40 wt% of the PTFE emulsion was added dropwise to a ZCNM-UiO-66-NH2 material suspension under ultrasonic conditions. The mixture was continuously sonicated, then frozen in liquid nitrogen. After thawing, the moisture was removed, and the mixture was dried to obtain the ZCNM-UiO-66-NH2-PTEF composite material based on PTFE-encapsulated MOFs.
[0079] Examples 51-54
[0080] Unlike Example 50, the amount of substances added in Examples 28-30 changed, as shown in Table 5.
[0081] Table 5. Changes in the Amount of Added Substances
[0082] Example 51 10 35 55 Example 52 15 40 35 Example 53 30 10 60 Example 54 10 20 70
[0083] Comparative Example 1
[0084] Preparation of S1 ZrO2 / CeO2 flexible nanofibers: 4.11 wt% cerium nitrate hexahydrate and 54.06 wt% zirconium oxychloride octahydrate were dissolved in a mixed solution of 15 g methanol and 2 g deionized water. 15.11 wt% potassium chloride and 26.72 wt% glutamine were added to the mixed solution. After heating to dissolve, the solution was concentrated to a viscous state and then burned in a furnace at 500℃. After combustion, the product was filtered and washed with deionized water until the conductivity of the washing solution was below 10 μS / cm. 2 Zirconia / cerium oxide nanopolymer crystals were obtained; the nanopolymer crystals were dissolved in a mixed solution of 20 mL dimethylformamide (DMF) and tetrahydrofuran (THF), and then 0.101 wt% polyacrylonitrile was added. After stirring until completely dissolved, the solution was left to stand overnight to form a precursor spinning sol. The precursor spinning sol was added to a syringe, and electrospinning was performed using a stainless steel needle at a feed rate of 0.84 mL / h, an applied spinning voltage of 12 kV, a spinning temperature of 25 °C, a spinning degree of 35%, and a receiving distance of 20 cm. ZrO2 / CeO2 precursor fibers were collected using a roller with a diameter of 50 mm, a translational speed of 10 mm / s, and a rotational speed of 600 r / min. The ZrO2 / CeO2 precursor fibers were gradually heated to 600℃ in a muffle furnace and held at that temperature for 2 hours to remove organic matter from the ZrO2 / CeO2 precursor fibers. The fibers were then allowed to cool naturally to obtain flexible ZrO2 / CeO2 nanofibers (ZCNM).
[0085] Preparation of S2 ZCNM-UiO-66-NH2 composite material: Based on the mass of ZCNM-UiO-66-NH2-PTEF composite material, 35 wt% of ZCNM was added and dissolved in 10 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF); 18.5 mmol of ZrCl4 and 18.5 mmol of 2-aminoterephthalic acid were dissolved in 70 mL of a mixed solution of dimethylformamide (DMF) and tetrahydrofuran (THF) (V:V = 50:50), and 59.2 mmol of hydrofluoric acid was added (the amount of hydrofluoric acid added was 3.2 times the molar amount of ZrCl4). A homogeneous solution was obtained by stirring at room temperature. 65 wt% of the homogeneous solution was added to the ZCNM solution. After ultrasonic treatment for 15 min, the obtained mixture was poured into a sealed 100 mL stainless steel autoclave with a polytetrafluoroethylene liner, and then placed in a vacuum drying oven at 120 °C for 50 h. The solid obtained after the reaction was washed three times with DMF and then three times with methanol. It was then dried in a vacuum drying oven at 80°C for 12 hours to obtain the ZCNM-UiO-66-NH2 composite material.
[0086] Example 55
[0087] The hydrophobicity of the composite materials obtained in Examples 50-54 and Comparative Example 1 was tested: the ZCNM-UiO-66-NH2-PTEF composite material and the ZCNM-UiO-66-NH2 composite material were placed on a glass slide and flattened, and tested using a contact angle meter.
[0088] The results are shown in Table 6. The best hydrophobicity was observed when the polytetrafluoroethylene (PTFE) emulsion accounted for 40 wt% of the ZCNM-UiO-66-NH2 composite material; Comparative Example 1, without PTFE emulsion as a coating material, exhibited the worst hydrophobicity. This is because PTFE, as a hydrophobic material, further combines with the ZCNM-UiO-66-NH2 composite material, not only preserving its inherent properties but also improving its water stability and hydrophobicity, resulting in the ZCNM-UiO-66-NH2-PTEF composite material with the strongest hydrophobicity.
[0089] Table 6. Hydrophobicity test results of MOF composites
[0090] CA(°) 158.1 156.2 143.2 144.0 132.5 116.7 Hydrophilicity Superhydrophobic hydrophobic hydrophobic hydrophobic hydrophobic hydrophobic
[0091] Example 56
[0092] Preparation of recyclable materials: The MOFs material obtained in Example 42 was used to adsorb microplastics onto a composite material. A sodium hydroxide solution with a pH of 10 was added, and the mixture was washed at 25°C for 10 minutes to remove the microplastics. The material was then washed multiple times with DMF and methanol, and dried in an oven at 40°C to obtain the recyclable material. The washed recyclable material was then subjected to another adsorption step for PS microplastics (800 nm), with the adsorption steps and conditions consistent with Example 49. The adsorption efficiency is as follows: Figure 3 As shown.
[0093] This invention conducted five cyclic adsorption experiments on the adsorbent. After five cycles, the adsorption efficiency remained above 80%, indicating that ZCNM-UiO-66-NH2-PTEF possesses good recycling capacity and excellent adsorption performance. The adsorption efficiency decreased by 12% after five cycles, possibly due to the leaching of the supported zirconium into the sodium hydroxide solution during desorption. By controlling the pH of the eluent, the adsorbed microplastics could be removed; this mechanism is related to the shift from physical adsorption to chemical adsorption at high pH values.
[0094] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing MOFs materials for removing microplastics from water, characterized in that: Includes the following steps: Preparation of S1 ZrO2 / CeO2 flexible nanofibers: 2.17-5.36 wt% cerium nitrate hexahydrate and 31.35-60.74 wt% zirconium oxychloride octahydrate were dissolved to obtain a mixed solution. A soluble salt and a carbonyl compound were added to the mixed solution, and the solution was heated to dissolve and concentrate to a viscous state. The solution was then combusted in a furnace and filtered and washed to obtain zirconium oxide / cerium oxide nanopolymer crystals. The nanopolymer crystals were dissolved in a mixed solution of DMF and THF, and polyacrylonitrile was added. The solution was stirred until completely dissolved and then allowed to stand to obtain a precursor spinning sol. The precursor spinning sol was electrospun to obtain ZrO2 / CeO2 precursor fibers. The precursor fibers were collected in a drum and then heated to 600°C in a muffle furnace to obtain flexible ZrO2 / CeO2 nanofibers ZCNM. The soluble salt is one of potassium chloride (KCl) and cesium chloride (CsCl); the carbonyl compound is one of glutamine and malonic anhydride. Preparation of S2 ZCNM-UiO-66-NH2 composite material: Based on the mass of ZCNM-UiO-66-NH2-PTFE composite material, 10-35 wt% of ZCNM was added and dissolved in 10 mL of a mixed solution of DMF and THF to obtain a ZCNM solution, wherein the volume ratio of DMF to THF in the mixed solution was 55-100:0-45; ZrCl4 and 2-aminoterephthalic acid in a molar ratio of 1:1 were dissolved in 70 mL of the mixed solution, and hydrofluoric acid with a molar amount of 1.1-3.2 times that of ZrCl4 was added, and the mixture was stirred at room temperature to obtain a homogeneous liquid; 10-65 wt% of the homogeneous liquid was added to the ZCNM solution, and the mixture was sonicated for 15 min, poured into a stainless steel autoclave, and the solid obtained after the reaction was washed and dried to obtain the ZCNM-UiO-66-NH2 composite material; Preparation of S3 ZCNM-UiO-66-NH2-PTFE composite material: 35-70wt% polytetrafluoroethylene emulsion was dropped into the ZCNM-UiO-66-NH2 composite material suspension under ultrasonic conditions, and ultrasonication was continued. The mixture was then placed in liquid nitrogen for freezing, thawed, and dried to remove moisture, thus obtaining the ZCNM-UiO-66-NH2-PTFE composite material. S4 Preparation of recyclable materials: MOFs material with adsorbed microplastics; adding sodium hydroxide solution to the MOFs material, washing and desorbing the microplastics, repeating 1-5 times; the pH value of the sodium hydroxide solution is 10; the washing time is 10 min.
2. The method for preparing MOFs materials for removing microplastics from water according to claim 1, characterized in that: The amount of KCl added is 14.23-31.34 wt%; the amount of CsCl added is 25.17-50.78 wt%; the amount of glutamine added is 15.49-36.59 wt%; and the amount of malonic anhydride added is 14.56-31.00 wt%.
3. The method for preparing MOFs materials for removing microplastics from water according to claim 1, characterized in that: The ZCNM addition amount in S2 is one of 10, 20, 30, or 35 wt%; the DMF and THF volume ratio is one of 55:45, 100:0, 60:40, 70:30, or 80:20; and the homogeneous liquid addition amount is one of 10, 20, 30, 35, 40, or 65 wt%.
4. The method for preparing MOFs materials for removing microplastics from water according to claim 1, characterized in that: The amount of hydrofluoric acid added in S2 is 3.2 times the molar amount of ZrCl4.
5. The method for preparing MOFs material for removing microplastics from water according to claim 1, characterized in that: The amount of polytetrafluoroethylene added in S3 is one of 35, 40, 55, 60, or 70 wt%.
6. The method for preparing MOFs materials for removing microplastics from water according to claim 1, characterized in that: The number of cycles described in S4 is one of 1, 2, 3, 4, or 5.
7. An application of MOFs material for removing microplastics from water, characterized in that: The MOFs material for removing microplastics from water is used in the removal of microplastics from water; the MOFs material for removing microplastics from water is obtained by the preparation method according to any one of claims 1-6; the pH of the water is 8-10.4, the type of microplastic is PS, and the diameter of the microplastic is 90nm-15μm; the zirconium oxide and cerium oxide are used in combination, so that the composite material is suitable for pH... The MOFs exhibit good stability within the range of 8-10.
4. The addition of ZCNM, DMF, THF, and the homogeneous liquid in a fixed ratio improves the dispersibility of the MOFs material, achieving a fiber diameter of 4.32 μm. The hydrofluoric acid adjusts the pore size, providing good adsorption capacity for PS microplastics in the 90 nm-15 μm range. The ZCNM-UiO-66-NH2-PTFE material prepared from polytetrafluoroethylene has a contact angle of 158° and good hydrophobicity. By controlling the pH of the sodium hydroxide solution to remove the microplastics already adsorbed by the MOFs material, the adsorption efficiency of the MOFs material can still reach over 80% after 5 cycles, demonstrating good recyclability.
Citation Information
Patent Citations
MOFs fiber membrane for adsorbing and intercepting micro-nano plastic in water and preparation method thereof
CN112755968A
Preparation and application of MOFs / graphite phase carbon nitride composite material with water system stability
CN114570334A
Metal organic framework-zirconium oxide fiber composite material, and preparation method and application thereof
CN111790355A
Composite material based on polytetrafluoroethylene-coated MOF material and preparation method of composite material
CN113943488A